2017
DOI: 10.1161/circulationaha.116.024602
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomics Implicates Modified Transfer RNAs and Altered Bioenergetics in the Outcomes of Pulmonary Arterial Hypertension

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
223
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(235 citation statements)
references
References 51 publications
12
223
0
Order By: Relevance
“…Further validation of predicted targets using a panel of 105 circulating plasma metabolites in PAH patients confirmed the association of right ventricular‐pulmonary vascular dysfunction with circulating indoleamine 2,3‐dioxygenase (IDO)‐dependent tryptophan metabolites (TMs), tricarboxylic acid intermediates and purine metabolites . Reports from recent study are also congruent with these findings where they demonstrate a strong strength of association between patient survival and metabolic profiles in PAH …”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Further validation of predicted targets using a panel of 105 circulating plasma metabolites in PAH patients confirmed the association of right ventricular‐pulmonary vascular dysfunction with circulating indoleamine 2,3‐dioxygenase (IDO)‐dependent tryptophan metabolites (TMs), tricarboxylic acid intermediates and purine metabolites . Reports from recent study are also congruent with these findings where they demonstrate a strong strength of association between patient survival and metabolic profiles in PAH …”
Section: Introductionmentioning
confidence: 59%
“…7 Reports from recent study are also congruent with these findings where they demonstrate a strong strength of association between patient survival and metabolic profiles in PAH. 8 However, the metabolic profile of individuals is dependent on race, sex and dietary habits. Till now, no studies focusing on the metabolomic changes in a primarily Chinese PAH patient cohort have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…22 Because of its physiological roles, circulating or urinary pseudouridine is considered a marker of RNA degradation and cell turnover. 23 Prior studies have reported higher concentrations of circulating pseudouridine in patients with pulmonary arterial hypertension, 24 heart failure, 25 impaired kidney function, 26,27 end-stage renal disease, 28,29 and cancer. 30 The relationships between circulating pseudouridine and posttranscriptional pseudouridylation of RNA and what role, if any, pseudouridine has in processes contributing to AF risk, requires further investigation.…”
Section: Bile Acids and Afmentioning
confidence: 99%
“…Histone deacetylases 1(HDAC1) was dramatically elevated in pulmonary arteries of human with pulmonary hypertension [27]. In PAH, plasma metabolomics approach showed modified transfer RNAs and altered bioenergetics [44].…”
Section: Genetics and Genomics Progress Of Pulmonary Hypertensionmentioning
confidence: 99%